On the improvement of the rotational structure analysis of 13CH3D ground vibrational state; Molecular Physics; Vol. 111, iss. 14-15: Dedicated to Martin Quack on the Occasion of his 65th Birthday - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bekhtereva E. S. Elena Sergeevna; Konova M. R.; Krivchikova Yu. V. Yuliya Valerjevna; Horneman V. -M. (2013, 2013)
Title screen